An Efficient One‐Pot Synthesis of Bis Butenolides. (20th September 2015) - Bayat, Mohammad; Fox, Joseph M.
Abstract : 3, 3′, 4, 4′‐Tetramethyl‐5, 5′‐dioxo‐2, 2′‐bifuran‐2, 2′(5 H, 5′ H ) diyl diacetate was obtained from the reaction between 2, 3‐dimethyl maleic anhydride andacetic anhydride in the presence of zinc in toluene. This easy synthetic route gave bis butenolide in excellent yield. Abstract :